Physical recovery, mental detachment and sleep as predictors of injury and mental energy. (November 2019) - Balk, Yannick A; de Jonge, Jan; Oerlemans, Wido GM; Geurts, Sabine AE
Although sports activities are generally considered beneficial to people's health and well-being, they can cause injuries and increased fatigue. Guided by the Demand-Induced Strain Compensation Recovery Model, this study hypothesized that physical recovery and mental detachment from sport-related activities would prevent injury and enhance mental energy. A cross-sectional survey study was conducted among 161 recreational athletes. Structural equation modelling analyses showed that mental detachment was negatively associated with injury and positively associated with mental energy. Sleep deprivation partially mediated the relation between mental detachment and mental energy. These findings imply an important role for mental detachment in maintaining people's health and well-being.